Intensification of photocatalytic decomposition of water by ultrasound - Singh A.; Sinha A.S.K. (My University, 2025)
Photocatalysis of water with and without ultrasound was studied using rGO supported CdS catalyst utilizing visible light. A higher hydrogen production was observed when ultrasound was used. This is attributed to a faster removal of bubbles of hydrogen from the surface of photocatalyst due to the mechanical energy associated with ultrasound overcoming surface tension. It has been further reported that the rate of hydrogen production decreased with time due to reversible deactivation of catalyst. This has been attributed to decrease in rate of hydrogen desorption with time. © 2017